2020
DOI: 10.1002/ejoc.202000752
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Chiral Cyclopentadienyl (Cpx) Metal Complexes in Asymmetric Catalysis

Abstract: Metal complexes containing cyclopentadienyl (Cp) ligands are versatile and robust catalysts widely applied in organic synthesis. During the last two decades chiral Cp x complexes have been applied in a variety of enantioselective transformations. Often associated with Group 9 metals (Co, Rh, Ir), chiral Cp x ligands have also been used in combination with early transition-metals and rare-earth elements. In this minireview asymmetric reactions that have been successfully steered

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(26 citation statements)
references
References 174 publications
0
26
0
Order By: Relevance
“…Rhodium catalysts with chiral cyclopentadienyl ligands have recently attracted a lot of attention thanks to their successful application in C-H activation reactions. [1][2][3][4][5][6] The most explored catalysts of this type are the binaphthyl derivatives 1 developed by Cramer et al and You et al, [7][8][9][10][11] the amino acid derivatives 2 developed by Antonchik and Waldmann et al, [12] the streptavidine-docked derivatives 3 developed by Ward and Rovis et al, [13,14] as well as some others [15][16][17][18][19][20] (Scheme 1). A wide application of these catalysts is still somewhat limited by their multistep synthesis involving rather expensive starting materials and reagents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rhodium catalysts with chiral cyclopentadienyl ligands have recently attracted a lot of attention thanks to their successful application in C-H activation reactions. [1][2][3][4][5][6] The most explored catalysts of this type are the binaphthyl derivatives 1 developed by Cramer et al and You et al, [7][8][9][10][11] the amino acid derivatives 2 developed by Antonchik and Waldmann et al, [12] the streptavidine-docked derivatives 3 developed by Ward and Rovis et al, [13,14] as well as some others [15][16][17][18][19][20] (Scheme 1). A wide application of these catalysts is still somewhat limited by their multistep synthesis involving rather expensive starting materials and reagents.…”
Section: Introductionmentioning
confidence: 99%
“…Rhodium catalysts with chiral cyclopentadienyl ligands have recently attracted a lot of attention thanks to their successful application in C–H activation reactions . The most explored catalysts of this type are the binaphthyl derivatives 1 developed by Cramer et al and You et al, the amino acid derivatives 2 developed by Antonchik and Waldmann et al, the streptavidine‐docked derivatives 3 developed by Ward and Rovis et al,, as well as some others (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…In parallel with this robust Cramer catalyst, SCpRh catalyst based on chiral 1,1'-spirobiindane scaffold [11] developed by our group [12a] also shown impressive reactivity and even better enantioselective induction in some cases. [12] Given our continuing interest in the development of Rhcatalyzed asymmetric CÀ H functionalizations, [13,14] we recently found that this CÀ H addition reaction could be realized by SCpRh catalyst with improved enantioselectivity (Scheme 1b). Here, we report the results of this study.…”
mentioning
confidence: 99%
“…Reduced yields were observed in the presence of AgBF 4 or AgPF 6 (entries 11-12, 27% and 32% yield). However, AgOAc and Ag 2 CO 3 were found to be invalid for this reaction (entries [13][14]. Finally, the optimized conditions were identified as follows: [SCpRh5 (5 mol%), AgSbF 6 (0.4 equiv) in DCE at 80°C (entry 5)].…”
mentioning
confidence: 99%
“… 7 In addition, enantioselective C–H functionalization using chiral Cp x ligands has been employed as an alternative strategy to access atropisomers. 8 Thus, Heller et al reported a Co-catalyzed enantioselective synthesis of axially chiral biaryls by means of [2+2+2] cycloaddition reactions, 9 You et al described an enantioselective dehydrogenative Heck coupling of biaryls with alkenes, 10 and Cramer et al achieved an Ir-catalyzed synthesis of axially chiral biaryl phosphines using diazonaphthoquinones. 11 We have described an intramolecular C–H functionalization of aromatic compounds with alkynes forming axially chiral 4-arylisoquinolones catalyzed by chiral Rh Jas Cp complexes, 12 and Li et al recently reported the use of chiral RhCp x complexes in the synthesis of axially chiral biindolyls.…”
mentioning
confidence: 99%